A DETERMINATION OF THE HALFLIFE OF CARBON 14 - JONES (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1950)
LANGERONIA macrocirra, a small fluke, just under 15 mm in lenght, from the intestine of Rana pipiens in Mexico, is descr; it differs from other genera of the subfamily, particularly in the size and position of the cirrus pouch, the position of the geni
PHYS REV D
Keywords: DETERMINATION, HALF, LIFE, CARBON 14; MULTIDISCIPLINARIA; QUIMICA INORGANICA; CARBONO